PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PREFERENSI RISIKO EKSEKUTIF, DAN CAPITAL INTENSITY PADA PENGHINDARAN PAJAK - Wiguna, I Putu Putra; Jati, I Ketut (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The realization of tax receipts in 2013-2015 with the target set not in accordance with the expected. This is due to the taxpayer's actions to minimize the tax burden or tax avoidance measures. Tax avoidance is an attempt made by the taxpayer (the company) to reduce or minimize the corporate tax burden. Tax avoidance is pro-duced with Effective Tax Rates (ETR). This study was conducted to determine the effect of corporate social responsibility, executive risk preference, and capital intensity on tax avoidance. This research was conducted at a manufacturing company listed on Indonesia Stock Exchange 2013-2015. Sampling using purposive sampling technique. Companies selected to sample as many as 44 companies after deducting sample determination criteria. Data analysis technique used in this research is multiple linear regression. The results showed that corporate social responsibility has a positive effect on tax avoidance, proving that the higher the company discloses corporate social responsibility the higher the company also doing tax avoidance action. Executive risk preferences also have a positive effect on tax avoidance, which means that executives are risk taker higher tax avoidance measures. Capital intensity has no effect on tax avoidance. The Government especially the Directorate General of Taxation in order to increase its supervision of tax avoidance practices, because the company that has been declared that has been carrying out CSR activities was still doing tax avoidance.